Implementasi game edukasi ZYLAND berbasis computational thinking untuk meningkatkan literasi numerasi siswa slow learner - Vio Arvendha; Rahadatul Aisy Tsamarah Ilyas; Suryani Elmaghfiroh; Ryani Dewi Nuraini; Dhandy Hananthiyo Ardhy Putra; Siti Azizah Susilawati (Nur Science Institute, 2026)
The objective of this community service project is to implement joyful learning through the ZYLAND educational game. This computational thinking-based tool is designed to enhance the literacy, numeracy, and concentration of 29 slow learner students at SD Negeri Wiropaten through digital educational games and Augmented Reality (AR) technology. The methods employed include empowerment, training, and technical assistance for the partners. The results indicate that ZYLAND had a positive impact, improving students' abilities in number recognition, simple addition, pattern comprehension, and logical decision making, accompanied by active participation, enthusiasm, and increased self-confidence among the slow learners. In terms of literacy and numeracy, letter and number recognition improved significantly from 40% to 75%, while proficiency in basic arithmetic and problem solving rose from 42% to 78%. Furthermore, students’ reading skills and comprehension improved, increasing from 38% to 73% following the program. Beyond academic aspects, this joyful learning medium also increased student concentration levels from 45% to 68% and strengthened their collaborative skills from 65% to 80%.